I-PASS Handoff Curriculum: Core Resident Workshop - Nancy Dollase Spector; Amy J. Starmer; April D. Allen; James F. Bale; Zia Bismilla; Sharon Calaman; Maitreya Coffey; F. Sessions Cole; Lauren Destino; Jennifer Everhart; Jennifer Hepps; Madelyn Kahana; et al. (Association of American Medical Colleges, 2013)
Abstract The Core Resident Workshop is the centerpiece of the I-PASS Curriculum Collection. The workshop features a 2-hour didactic and interactive session devoted to team training in structured communication techniques, and to the teaching of a standardized approach to the handoff process (including the integration of oral and written handoff components). Key structured team communication techniques and the I-PASS mnemonic are taught in detail and reinforced with the use of trigger videos and large group discussion. Ideally this 2-hour session is followed by the 1-hour handoff simulation exercises which features small group interactive role-plays in which participants gain hands-on experience and practice the I-PASS handoff technique. This workshop is also suitable for a faculty educational retreat. In brief, we found in a detailed review of 10,740 patient admissions that a 23% reduction in medical errors and a 30% reduction in injuries due to medical errors (preventable adverse events) occurred following implementation of the I-PASS Handoff Bundle in nine academic medical centers. In direct observation of thousands of hours of resident workflow (time motion analysis) before and after implementation of the program, conducting handoffs using the I-PASS method was found to require no more time per handoff, and resident workflow throughout the shift was likewise unchanged, including no change in the amount of time spent at the computer or in direct patient care.